Effect of Tea and Mango Mistletoe Extract as Dietary Adjuvant on Triglyceride in Wistar Rats - Tania Putri Nur Yasinta; Nour Athiroh Abdoes Sjakoer; Ari Hayati (Jurnal Ragam Pengabdian, 2026)
The increasing prevalence of obesity in Indonesia has contributed to a rise in metabolic disorders, including hypertriglyceridemia, which is a major risk factor for cardiovascular and metabolic diseases. Therefore, safe and effective natural- based therapeutic alternatives are needed. This study aimed to evaluate the effect of a combined extract of tea mistletoe (Scurrula atropurpurea) and mango mistletoe (Dendrophthoe pentandra) leaves as a dietary adjuvant on serum triglyceride levels in male Wistar rats (Rattus norvegicus) induced with a high- fat diet. This experimental study employed a randomized pre-test post-test control group design with five groups: negative control, positive control (high-fat diet), and three treatment groups receiving the combined extract at doses of 50, 100, and 200 mg/kg body weight (n = 7 per group). The treatment was administered orally for 37 days. Serum triglyceride levels were measured using the Colorimetric Enzymatic Test (Glycerol Phosphate Oxidase method) and analyzed using one-way analysis of variance (ANOVA). The results demonstrated a statistically significant difference in triglyceride levels among the groups (p = 0.01024). The positive control group exhibited the highest mean triglyceride level, whereas administration of the combined mistletoe extract resulted in a reduction in triglyceride levels. The most pronounced decrease was observed in the group receiving 100 mg/kg body weight, which showed the lowest mean triglyceride level among the treatment groups. The hypolipidemic effect of the combined extract is presumed to be associated with the presence of bioactive compounds such as flavonoids and polyphenols, which possess antioxidant properties and play a role in lipid metabolism regulation. In conclusion, the combined extract of tea mistletoe and mango mistletoe has potential as a natural dietary adjuvant for lowering triglyceride levels and improving lipid profiles in conditions of high-fat diet–induced dyslipidemia.